The Impact of Team-Based Learning on Anxiety Among Graduate Students in a Data Science Master's Program - Andrea Marques; Maria Anastasiadou; Roberto Henriques (Emerging Science Journal, 2025)
Objectives: This study aims to explore the impact of Team-Based Learning (TBL) on anxiety levels (AL) among master's students in Data Science, particularly how TBL influences students' anxiety in academic settings and contributes to their engagement, skill development, and learning awareness. Methods/Analysis: The study implemented TBL in a Data Science master's course for one semester, employing both qualitative and quantitative methods. Data were collected through surveys and individual interviews, followed by exploratory and statistical analyses conducted in Jupyter Notebook, SPSS Statistics, and Excel. This mixed-methods approach provided comprehensive insights into students' experiences and perceptions regarding TBL and anxiety. Findings: The analysis revealed that TBL positively affects students' anxiety levels, contributing to enhanced engagement, individual and group skills, and awareness of the learning process. However, certain TBL elements were found to potentially increase anxiety, suggesting a need for tailored adjustments to the approach. Novelty/Improvement: This study underscores TBL's potential to reduce anxiety and foster active learning, emphasizing the importance of student-centered teaching. It highlights specific TBL components that may require modification to minimize negative impacts on student anxiety, offering valuable guidance for educators aiming to create a supportive and effective learning environment. Doi: 10.28991/ESJ-2025-SIED1-01 Full Text: PDF